Pengaruh Macam Dan Konsentrasi Insektisida Hama Ulat Grayak (Spodoptera Frugiperda) Terhadap Pertumbuhan dan Produksi Tanaman Jagung Manis (Zea Subsp. Mays) - Rizky Surya Abadi; Tjatur Prijo Rahardjo; Muhammad Muharram (JINTAN : Jurnal Ilmiah Pertanian Nasional, 2022)
Sweet corn is a commodity for seasonal crops and food crops. In addition, this plant is also included in the cereal plant and is widely eaten by residents after rice plants. Sweet corn has a sweeter taste than other corn, so it is usually eaten when still young. The experiment was aimed to determine the interaction between several types and concentrations of armyworm insecticides on the growth and production of sweet corn plants. It was conducted at the Faculty of Agriculture, Kadiri University, from February to March 2021. The experimental design used in this study was a 5 x 2 factorial randomized block design with three replications. 2 factors were examined, namely the type of insecticide and the concentration of insecticides. Research results showed a combination of treatment and insecticide concentration of armyworm pests. There was an interaction with the sweet corn stalk diameter parameters. The best treatment was found in the Sidasat Insecticide (M4) with a concentration of 1gr/l. And found in the results of the study of giving a combination of insecticide treatment and the concentration of armyworms at the age of 30SHT, the best treatment was found in the combination treatment of chemical insecticides (M4K1) Sidasat with a concentration of 1gr/ which is 11.96% pest attack rate on corn plants. The combination of treatments and concentration of armyworm insecticide solution on maize showed no interaction with the cob's length, diameter, and weight. The combination of insecticide treatment and dose did not affect the production of sweet corn.Jagung manis memiliki ciri kas rasa yang lebih manis dari pada jagung yang lain. Komoditas jagung manis tergolong tanaman semusim dengan umur yang sangat pendek, sehingga dalam budidayanya diperlukan penanganan lebih extra, terutama pada kegiatan pengendalian hama. Keberadaan hama baru Spodoptera frugiperdaÂ berpotensi dalam menurunkan produksi jagung karena intensitas serangannya sangat cepat. Percobaan ditujukan untuk mengetahui interaksi antara beberapa macam dan konsentrasi insektisida hama ulat grayak, terhadap pertumbuhan dan produksi tanaman jagung manis. Uji coba dilakukan di lahan percobaan Fakultas Pertanian Universitas Kadiri. Rancangan percobaan yang digunakan dalam penelitian ini adalah Rancangan Acak Kelompok (RAK) pola faktorial 5x2, dengan 3 ulangan. Faktor pertama adalah macam isektisidaM1= Bt Plus (Bacillus sp), M = Metarizep (Bauveria s.), M =Proclaim (Emmamectin Benzoat 5%) M4= Sidasat (Asefat 75%) M5= Winder (Imidakloprid 75%). Faktor kedua konsentrasi larutan insektisida (K), yaitu: K1= 1 gr/liter K2= 3 gr/liter. Hasil penelitian menunjukkan kombinasi perlakuan macam dan konsentrasi insektisida hama ulat grayak terjadi interaksi terhadap parameter panjang, diameter, dan bobot tongkol jagung manis. Perlakuan terbaik pada insektisida sidasat (M4). Kombinasi perlakuan insektisida kimia (M4K1) sidasat dengan konsentrasi 1gr/ dapat menurunkan intensitas serangan hama ulat gerayak hingga 11,96%.